2016
DOI: 10.1080/13546805.2015.1127222
|View full text |Cite
|
Sign up to set email alerts
|

Attention and memory bias to facial emotions underlying negative symptoms of schizophrenia

Abstract: Attention bias away from emotional information relatively early in the attentional process and associated diminished positive memory may relate to pathological mechanisms for negative symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…It should be noted that the PHs retained the operational mechanism of CPs as a compensatory reaction. Nonetheless, it is plausible that the rigidity of aberrant information processing [49,54] (e.g., attention bias with misattributions of negative emotions and deranged early perceptual processing) [55] in actively hallucinating SPs may eventually lead to abnormal neurocognition, as expressed in poor EI performance in the PH group [56].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the PHs retained the operational mechanism of CPs as a compensatory reaction. Nonetheless, it is plausible that the rigidity of aberrant information processing [49,54] (e.g., attention bias with misattributions of negative emotions and deranged early perceptual processing) [55] in actively hallucinating SPs may eventually lead to abnormal neurocognition, as expressed in poor EI performance in the PH group [56].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to different stimuli being used in the attentional tasks (pictures) and the recall task (words). Follow‐up studies used a similar type of stimuli in attention and memory tasks and found a coherence of attention and memory biases in the same populations (Jang, Park, Lee, Cho, & Choi, 2016; Matusz, Traczyk, Sobkow, & Strelau, 2015). Indeed, Everaert, Duyck, and Koster (2014) suggested that attention and memory are not independent processes but closely interlinked.…”
mentioning
confidence: 95%
“…In Korea, various face databases comprising only of static face stimuli have been developed and used in a number of studies. For example, the Korea University Facial Expression Collection (KUFEC; Kim et al, 2011) was used to examine the facial recognition ability of clinical populations (Jung et al, 2015; Jang et al, 2016; Kim and Kim, 2016) and the differences in perceiving facial expressions in a non-clinical adult group (Kim et al, 2013). Recently, KUFEC-II, a revised version of KUFEC, has been developed to overcome the limitations of KUFEC in its shooting and selection of stimuli by adopting the Facial Action Coding System (FACS; Ekman et al, 2002) Some Korean databases, such as Extended ChaeLee (Lee et al, 2013) and the Korean Facial Expressions of Emotion (KOFEE) database (Park et al, 2011) have been used in many neuroscience studies with emphasis on the facial perception skills of clinical populations (Kim et al, 2014; Lee et al, 2015; Oh et al, 2016; Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%